What is the appropriate pricing mechanism for China's renewable energy in a new era?. (January 2022) - Zhao, Xiaoli; Zhong, Zewei; Gan, Chao; Yan, Fengguang; Zhang, Sufang
Highlights: The revenue and curtailment of wind power are analyzed under three pricing mechanisms. After 2019, the fully competitive pricing mechanism is appropriate for China's wind power. The introduction of the competitive pricing mechanism improves social welfare. Market-oriented electricity pricing mechanism needs to be further enhanced in China. Abstract: Along with the cost reduction and the scaling up of renewable energy, China is phasing out its feed-in tariff (FIT) approach, a fixed pricing mechanism which has been applied to China's wind and solar power for over a decade. Meanwhile, electricity price deregulation is an important part of China's ongoing power sector reform and is very likely to have a significant impact on renewable energy development in the country. This paper studies the appropriate electricity pricing mechanism for renewable energy in the aforesaid new era from both theoretical and empirical perspectives by taking wind power as a case study. The main conclusions are that, with decreasing wind power cost, the premium pricing mechanism was appropriate for China's wind power during the period between 2010 and 2018, and a fully competitive pricing mechanism can be adopted for wind power in China after 2019 when wind power cost can be fully recovered. It is also found that China's electricity market reform has positive impacts on mitigating wind power curtailment and increasing social welfare. Policy implications are provided at the end of the paper.